The influence of foreign, busy board members, and gender diversity on firm bankruptcy - Abdulaziz S. Al Naim; Abdullah A. Aljughaiman; Abdulateif A. Almulhim; Abdulmohsen K. Alosaimi (Cogent Business & Management)
This study examines the impact of three key board characteristics—foreign board members, busy board members, and gender diversity—on firm bankruptcy among companies listed on the Saudi Stock Exchange. The sample consists of 994 firm-year observations of non-financial firms from 2015 to 2023. The Altman Z-score is used as a proxy for bankruptcy. We employ OLS and Tobit as our main estimation models due to the unique nature of our dependent variable. Our findings reveal a positive and significant relationship between the percentage of female board members, board busyness, board independence, board size, and the Altman Z-score, indicating that larger boards with more female, busy, and independent members have a lower bankruptcy risk. Conversely, the percentage of non-Saudi board members is negatively associated with the Altman Z-score. Therefore, more foreign members on firms’ boards lead to more bankruptcy risk. The findings inform Saudi regulators on enhancing corporate governance and board effectiveness to support the structure of finances in Saudi firms. The positive impact of board busyness challenges common concerns about excessive directorships, suggesting that retaining experienced busy directors could benefit Saudi firms. However, our findings also indicate that non-Saudi board members can pose risks, which policymakers need to address.